2019
DOI: 10.1002/epi4.12353
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous KCNQ3 loss‐of‐function variant causes non‐syndromic intellectual disability and neonatal‐onset pharmacodependent epilepsy

Abstract: Objective Heterozygous variants in KCNQ2 or, more rarely, KCNQ3 genes are responsible for early‐onset developmental/epileptic disorders characterized by heterogeneous clinical presentation and course, genetic transmission, and prognosis. While familial forms mostly include benign epilepsies with seizures starting in the neonatal or early‐infantile period, de novo variants in KCNQ2 or KCNQ3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…When recorded the HEK293 cells without transfected KCNQ2, the currents closely resembled those for homomeric S247X, which indicated that homomeric S247X was not functional in the present study. That is compatible with S247X by nonsense-mediated mRNA decay [46][47][48] and removing all C-terminal domain for tetramerisation of functional channels, is supposed to be nonfunctional. HEK 293 cells have been widely used in cell biology and the gene expression in HEK 293 cells is like that of the neuron.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When recorded the HEK293 cells without transfected KCNQ2, the currents closely resembled those for homomeric S247X, which indicated that homomeric S247X was not functional in the present study. That is compatible with S247X by nonsense-mediated mRNA decay [46][47][48] and removing all C-terminal domain for tetramerisation of functional channels, is supposed to be nonfunctional. HEK 293 cells have been widely used in cell biology and the gene expression in HEK 293 cells is like that of the neuron.…”
Section: Discussionmentioning
confidence: 86%
“…The hypothesis is verified in clinical phenotypes for which seizures improved after the age of 1 month. We predict that the S247X nonsense mutation caused a lower expression of the KCNQ2 protein due to nonsense-mediated mRNA decay [46][47][48] , which activated hetero-KCNQ2 and KCNQ3 functional compensation. However, a decrease in the expression of the KCNQ2 protein in S247L and S247W was not predicted.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of KCNQ2-E is reported to be 1-3/100.000 births (Lopez-Rivera et al, 2020). By contrast, only a handful of DEE patients with pathogenic variants in KCNQ3 or KCNQ5 have been described (Rauch et al, 2012;Epi4k Consortium et al, 2013;Lehman et al, 2017;Ambrosino et al, 2018;Kothur et al, 2018;Lauritano et al, 2019;Rosti et al, 2019;Sands et al, 2019).…”
Section: Human Pathogenic Kcnq2 Variants and Neurodevelopmentmentioning
confidence: 99%
“…During the last decade, an emerging number of studies pointed out that severe disruption of the function of Kv7.2, Kv7.3, and Kv7.5 subunits due to de pathogenic variants in the encoding gene leads to developmental and epileptic encephalopathy (DEE;Weckhuysen et al, 2012;Lehman et al, 2017;Lauritano et al, 2019). DEEs are a heterogeneous group of mostly neonatal-, infantile-or childhood-onset disorders characterized by severe, drug-resistant seizures, characteristic electroencephalographic (EEG) signatures, and different levels of developmental delay or regression, often with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several pieces of evidence support this view; as an example, while heterozygous frameshift variants in KCNQ2 are frequent causes of BFNE (Miceli et al, 2018), no heterozygous pathogenic frameshift KCNQ3 variant has ever been associated with a human phenotype. In addition, no individual carrying KCNQ2 frameshift variants in homozygosity has ever been described, as minimal KCNQ2 residual activity is probably essential for survival (Lauritano et al, 2019); by contrast, two recent studies reported the occurrence of homozygous frameshift variants in KCNQ3 (each inherited from an asymptomatic parent) in patients with developmental delay and neonatal seizures (Kothur et al, 2018;Lauritano et al, 2019), demonstrating that, homozygous variants in KCNQ3 are compatible with life. Moreover, a distinct functional role of these two genes emerging from developmental and genetic studies in humans, appears also to be recapitulated in mice.…”
Section: Discussionmentioning
confidence: 99%